Financial Performance Analysis Before and During the Covid-19 Pandemic: Analisis Kinerja Keuangan Sebelum dan Saat Pandemi Covid-19 - Arto, Thoriqi Juni; Setiyono, Wisnu Panggah (Indonesian Journal of Innovation Studies, 2022)
Financial performance is a description of the company's financial condition in a certain period regarding aspects of fund raising and distribution of funds, which are usually measured by indicators of solvency, profitability, liquidity, and activity. This study aims to determine differences in the performance of the solvency ratio (DER), profitability ratio (ROA), liquidity ratio (CR), and activity ratio (TATO) before and during the covid-19 pandemic. Estates listed on the Indonesia Stock Exchange (IDX) During the period of 2019 and 2020. The method of determining the sample in this study is using the purposive sampling method so that the number of samples obtained is 23 companies. The results of the study include DER(0,368>0,05) and ROA(0,427>0,05) are accepted because statistically there is no difference before and during the Covid-19 pandemic, while CR(0.002) < i0.05) and TATO (0.023 < 0.05) were rejected because statistically there were differences before and during the Covid-19 pandemic.